Creek or Crick? - Jim Hoy (Symphony in the Flint Hills, 2018)
Introduction: What do you call a running stream of water that’s smaller than a river but larger than a brook? Many would say it’s a creek (rhymes with peek), but others would call it a crick (rhymes with pick). Then there are those, myself included, who use both terms.